Fully biodegradable composite material as well as preparation method and application thereof

By using natural raw materials such as bamboo nanopowder to form a three-dimensional network structure, a fully biodegradable composite material has been developed, which solves the problems of high cost of existing bio-based plastics and poor water resistance of starch materials. It achieves rapid and complete degradation and good mechanical properties, and is suitable for agricultural mulch film and food packaging.

CN121699256APending Publication Date: 2026-03-20YANTAI JIAHE PLASTIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610113326.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-28
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Existing bio-based plastics are expensive, require harsh and incomplete degradation conditions, and pure starch materials have poor water resistance and low mechanical strength. Traditional modification methods sacrifice the materials' full biodegradability and environmental friendliness.

Method used

Using natural raw materials such as bamboo nanopowder, carboxymethyl starch, cellulose nanocrystals, sodium citrate, sodium hydroxide, and sodium trimetaphosphate, a three-dimensional network structure is formed through green physical/chemical cross-linking technology to prepare a fully biodegradable composite material.

Benefits of technology

The prepared composite material degrades rapidly and completely in natural environments without leaving any environmental residues. It possesses excellent mechanical properties and water resistance, is inexpensive, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a fully biodegradable composite material as well as a preparation method and application thereof, and belongs to the technical field of biodegradable materials. The fully biodegradable composite material is prepared from the following components in percentage by mass: 32 to 36 percent of bamboo nano powder, 48 to 52 percent of carboxymethyl starch, 3 to 5 percent of cellulose nanocrystals, 5 to 7 percent of sodium citrate, 1 to 3 percent of sodium hydroxide and 1 to 4 percent of sodium trimetaphosphate. The fully biodegradable composite material is composed of natural and renewable biomass raw materials, does not contain any fossil-based polymer, and forms a three-dimensional network structure through a green physical / chemical crosslinking technology, and the final product can be rapidly and completely degraded in a natural environment or a composting condition without environmental residues; and the prepared composite material has good mechanical properties, water resistance and biodegradability, can be widely applied to the environmental protection fields of agricultural mulching films, food packaging and the like, and fundamentally solves the problem of white pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a fully biodegradable composite material, its preparation method, and its application, belonging to the field of biodegradable materials technology. Background Technology

[0002] Plastic pollution, particularly the white pollution caused by agricultural mulch films and disposable packaging materials, has become a global environmental challenge. Traditional polyethylene (PE) mulch films are difficult to degrade in the natural environment, and their residues in the soil can lead to soil structure damage and fertility decline. Although bio-based plastics such as polylactic acid (PLA) and polyhydroxyalkanoates (PHA) have been commercialized, they are expensive, have relatively harsh degradation conditions, and their production processes are not entirely green.

[0003] Starch-based materials have attracted much attention due to their wide availability and complete biodegradability; however, pure starch materials suffer from fatal flaws such as poor water resistance and low mechanical strength. Current technologies modify starch by adding fossil-based polymers, such as polyvinyl alcohol or synthetic plastic additives, but this sacrifices, to some extent, the material's complete biodegradability and environmental friendliness.

[0004] Therefore, developing a composite material whose raw materials are all derived from renewable resources, whose preparation process is green and environmentally friendly, and which has both good mechanical properties and rapid and complete degradation characteristics is of great practical significance and market demand. Summary of the Invention

[0005] The purpose of this invention is to provide a fully biodegradable composite material, its preparation method, and its application to solve the technical problems existing in the prior art as described above.

[0006] One of the objectives of this invention is to provide a fully biodegradable composite material, comprising the following components by mass percentage: 32-36% bamboo nanopowder, 48-52% carboxymethyl starch, 3-5% cellulose nanocrystals, 5-7% sodium citrate, 1-3% sodium hydroxide, and 1-4% sodium trimetaphosphate.

[0007] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, the particle size of the bamboo nanopowder is 50~200 nanometers.

[0008] The second objective of this invention is to provide a method for preparing a fully biodegradable composite material, comprising the following steps: (1) Preparation of gelatinized starch slurry: Carboxymethyl starch, sodium citrate, sodium hydroxide and sodium trimetaphosphate are added to a preheated liquid medium and mechanically stirred at 300~500 rpm for 20~40 minutes to form a homogeneous gelatinized starch slurry; (2) Preparation of nano slurry: bamboo nanopowder and cellulose nanocrystals are slowly added to the obtained gelatinized starch slurry. The mixture is first stirred at low speed for initial mixing, and then transferred to a high-speed shear homogenizer for homogenization at 800~1200 rpm for 5~15 minutes to obtain a uniformly dispersed nano slurry. (3) Preparation of mixed slurry: The obtained nano slurry is transferred to a reaction vessel and crosslinked under water bath conditions of 70~85℃ and stirring continuously at a speed of 200~400pm to obtain a mixed slurry; (4) Molding: The mixed slurry is poured onto a smooth substrate by casting, and the thickness is controlled to be 0.05~0.5mm. Then it is placed in a drying oven at 50~70℃ for casting, or the mixed slurry is injected into a mold for injection molding. (5) Post-processing: The molded material is removed and placed in a constant temperature and humidity chamber for equilibration treatment for at least 24 hours to obtain the fully biodegradable composite material.

[0009] Further, in step (1), the liquid medium is a mixture of deionized water and a homogenized solution of carboxymethyl cellulose with a mass fraction of 1% at a volume ratio of 1:1. The amount of the liquid medium is 2.5 to 3.5 times the total mass of bamboo nanopowder, carboxymethyl starch, cellulose nanocrystals, sodium citrate, sodium hydroxide and sodium trimetaphosphate. The preheating temperature of the liquid medium is 50 to 60°C.

[0010] Furthermore, in step (2), the low-speed stirring speed is 300~500 rpm.

[0011] Furthermore, in step (3), the cross-linking reaction takes 30 to 90 minutes.

[0012] Further, in step (4), the substrate is a glass plate or a polyester film.

[0013] Furthermore, in step (5), the temperature of the constant temperature and humidity chamber is 20~25℃ and the humidity is 45~55%.

[0014] The third objective of this invention is to provide an application of the above-mentioned fully biodegradable composite material in the preparation of agricultural mulch films.

[0015] The fourth objective of this invention is to provide an application of the above-mentioned fully biodegradable composite material in the preparation of food packaging materials.

[0016] The technical solution provided by this invention has the following advantages compared with the prior art: 1. The fully biodegradable composite material of the present invention is composed of natural renewable biomass raw materials, contains no fossil-based polymers, and forms a three-dimensional network structure through green physical / chemical cross-linking technology. The final product can be rapidly and completely degraded in natural environment or composting conditions, leaving no environmental residue. Furthermore, the main raw materials, bamboo nanopowder and carboxymethyl starch, are widely available and inexpensive, giving it a significant cost competitiveness compared to fully synthetic biodegradable plastics.

[0017] 2. The preparation method of the present invention uses an aqueous solution as a medium, without the participation of harmful or toxic solvents, and the reaction conditions are mild and energy consumption is low, which is in line with the principles of green chemistry. The composite slurry prepared in the process has good rheological properties and is easy to form into a film by casting or injection molding, making it suitable for continuous industrial production.

[0018] 3. The fully biodegradable composite material of this invention uses bamboo nanopowder as a rigid reinforcement and cellulose nanocrystals as a nano-reinforcing agent and interfacial compatibilizer. The two work synergistically to significantly improve the mechanical properties of the starch matrix. Sodium trimetaphosphate is used as a crosslinking agent to react with the hydroxyl groups in carboxymethyl starch, and sodium citrate is used as a plasticizer to assist crosslinking, together constructing a stable three-dimensional network structure, effectively inhibiting the rehydration and swelling of starch, and greatly improving the water resistance of the composite material. Sodium hydroxide creates an alkaline environment for the reaction between sodium trimetaphosphate and carboxymethyl starch, activates the hydroxyl groups on the carboxymethyl starch molecules, further promotes the crosslinking reaction, and acts as a gelatinization promoter by breaking the hydrogen bonds inside the carboxymethyl starch to form a homogeneous slurry.

[0019] 4. The fully biodegradable composite material prepared by this invention has good mechanical properties, water resistance and biodegradability, and can be widely used in environmental protection fields such as agricultural mulch film and food packaging, fundamentally solving the problem of "white pollution". Detailed Implementation

[0020] The principles and features of the present invention are described below with reference to examples. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Example 1

[0021] A fully biodegradable composite material comprises the following components: 34 grams of bamboo nanopowder, 52 grams of carboxymethyl starch, 6 grams of sodium citrate, 4 grams of cellulose nanocrystals, 2 grams of sodium hydroxide, and 2 grams of sodium tripolyphosphate.

[0022] A method for preparing a fully biodegradable composite material includes the following steps: (1) Preparation of gelatinized starch slurry: Carboxymethyl starch, sodium citrate, sodium hydroxide and sodium trimetaphosphate were added to 300g of liquid medium (deionized water and 1% sodium carboxymethyl cellulose homogenate were mixed at a volume ratio of 1:1) preheated to 55℃, and mechanically stirred at 400rpm for 30 minutes to form a homogeneous gelatinized starch slurry. (2) Preparation of nano slurry: bamboo nanopowder and cellulose nanocrystals were slowly added to the obtained gelatinized starch slurry. The mixture was first stirred at a low speed of 400 rpm for initial mixing, and then transferred to a high-speed shear homogenizer for homogenization at a speed of 1000 rpm for 10 minutes to obtain a uniformly dispersed nano slurry. (3) Preparation of mixed slurry: The obtained nano slurry was transferred to a reaction vessel and crosslinked for 60 minutes under the conditions of a water bath at 75°C and a stirring speed of 300 pm to obtain a mixed slurry; (4) Molding: The mixed slurry is poured onto a smooth glass plate by casting, the thickness is controlled to be 0.1 mm, and then placed in a 60°C forced-air drying oven for casting. (5) Post-processing: The molded material is removed and placed in a constant temperature and humidity chamber at 23°C and 50% for equilibration treatment for 24 hours to obtain the fully biodegradable composite material. Example 2

[0023] A fully biodegradable composite material comprises the following components: 32g bamboo nanopowder, 52g carboxymethyl starch, 5g sodium citrate, 5g cellulose nanocrystals, 3g sodium hydroxide, and 3g sodium tripolyphosphate.

[0024] The preparation method is the same as in Example 1, except that in step (3), the temperature of the water bath is 80°C. Example 3

[0025] A fully biodegradable composite material comprises the following components: 36 grams of bamboo nanopowder, 48 grams of carboxymethyl starch, 7 grams of sodium citrate, 3 grams of cellulose nanocrystals, 2 grams of sodium hydroxide, and 4 grams of sodium tripolyphosphate.

[0026] The preparation method is the same as in Example 1, except that in step (3), the crosslinking reaction time is 45 minutes. Example 4

[0027] A fully biodegradable composite material comprises the following components: 34 grams of bamboo nanopowder, 52 grams of carboxymethyl starch, 6 grams of sodium citrate, 4 grams of cellulose nanocrystals, 2 grams of sodium hydroxide, and 2 grams of sodium tripolyphosphate.

[0028] The preparation method is the same as in Example 1, except that in step (4), the thickness of the cast film is 0.25 mm. Example 5

[0029] A fully biodegradable composite material comprises the following components: 34 grams of bamboo nanopowder, 52 grams of carboxymethyl starch, 6 grams of sodium citrate, 4 grams of cellulose nanocrystals, 2 grams of sodium hydroxide, and 2 grams of sodium tripolyphosphate.

[0030] The preparation method is the same as in Example 1, except that in step (4), the mixed slurry is injected into the mold of the biscuit tray and dried and molded at 65°C.

[0031] Comparative Example 1 Pure starch film, using only 100g of carboxymethyl starch.

[0032] Preparation method: Direct gelatinization followed by casting and drying, with a casting thickness of 0.1 mm.

[0033] Comparative Example 2 A fully biodegradable composite material comprises the following components: 34 grams of bamboo nanopowder, 52 grams of carboxymethyl starch, 7 grams of sodium citrate, 4 grams of cellulose nanocrystals, and 3 grams of sodium hydroxide.

[0034] The preparation method is the same as in Example 1.

[0035] Comparative Example 3 A fully biodegradable composite material comprises the following components: 36 grams of bamboo nanopowder, 52 grams of carboxymethyl starch, 5 grams of cellulose nanocrystals, 3 grams of sodium hydroxide, and 4 grams of sodium tripolyphosphate.

[0036] The preparation method is the same as in Example 1.

[0037] Comparative Example 4 A fully biodegradable composite material comprising the following components: 34 g bamboo nanopowder, 52 g carboxymethyl starch, 6 g sodium citrate, 4 g cellulose nanocrystals, and 4 g sodium tripolyphosphate.

[0038] The preparation method is the same as in Example 1.

[0039] Comparative Example 5 A fully biodegradable composite material comprises the following components: 36 grams of bamboo nanopowder, 52 grams of carboxymethyl starch, 6 grams of sodium citrate, 3 grams of sodium hydroxide, and 3 grams of sodium tripolyphosphate.

[0040] The preparation method is the same as in Example 1.

[0041] Comparative Example 6 A fully biodegradable composite material comprises the following components: 30g bamboo nanopowder, 54g carboxymethyl starch, 6g sodium citrate, 6g cellulose nanocrystals, 2g sodium hydroxide, and 2g sodium tripolyphosphate.

[0042] The preparation method is the same as in Example 1.

[0043] Comparative Example 7 A fully biodegradable composite material comprises the following components: 38 grams of bamboo nanopowder, 46 grams of carboxymethyl starch, 8 grams of sodium citrate, 4 grams of cellulose nanocrystals, 2 grams of sodium hydroxide, and 2 grams of sodium tripolyphosphate.

[0044] The preparation method is the same as in Example 1.

[0045] Comparative Example 8 A fully biodegradable composite material comprises the following components: 38 grams of bamboo nanopowder, 46 grams of carboxymethyl starch, 5 grams of sodium citrate, 3 grams of cellulose nanocrystals, 3 grams of sodium hydroxide, and 5 grams of sodium tripolyphosphate.

[0046] The preparation method is the same as in Example 1.

[0047] Performance testing: The materials obtained in Examples 1-5 and Comparative Examples 1-8 were subjected to the following performance tests. The test results are shown in Table 1.

[0048] Tensile strength test: The test method refers to GB / T 1040.3-2006; 2. Elongation at break test: The test method refers to GB / T 1040.3-2006; 3. Degradation rate test: The test method refers to GB / T 19277-2003; 4. Permeability test: The test method refers to GB / T 1037-2021.

[0049] Table 1 Performance Test Results

[0050] The fully biodegradable composite film prepared in Example 2 was tested for its preservation effect on apples at room temperature. The results showed that the film could regulate the microenvironment inside the packaging, effectively reducing the spoilage rate of apples and extending shelf life by 3-5 days compared to PE preservation film. The biscuit tray obtained by injection molding in Example 5 has a certain degree of hardness and support, and can be used to hold dry foods, etc., and completely degrades within 30 days under home composting conditions. This indicates that the fully biodegradable composite material prepared using the method of this invention can be used to prepare food packaging materials.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A fully biodegradable composite material, characterized in that, By mass percentage, it includes the following components: bamboo nanopowder 32-36%, carboxymethyl starch 48-52%, cellulose nanocrystals 3-5%, sodium citrate 5-7%, sodium hydroxide 1-3%, and sodium trimetaphosphate 1-4%.

2. The fully biodegradable composite material according to claim 1, characterized in that, The bamboo nanopowder has a particle size of 50~200 nanometers.

3. A method for preparing a fully biodegradable composite material as described in claim 1 or 2, characterized in that, Includes the following steps: (1) Preparation of gelatinized starch slurry: Carboxymethyl starch, sodium citrate, sodium hydroxide and sodium trimetaphosphate are added to a preheated liquid medium and mechanically stirred at 300~500 rpm for 20~40 minutes to form a homogeneous gelatinized starch slurry; (2) Preparation of nano slurry: bamboo nanopowder and cellulose nanocrystals are slowly added to the obtained gelatinized starch slurry. The mixture is first stirred at low speed for initial mixing, and then transferred to a high-speed shear homogenizer for homogenization at 800~1200 rpm for 5~15 minutes to obtain a uniformly dispersed nano slurry. (3) Preparation of mixed slurry: The obtained nano slurry is transferred to a reaction vessel and crosslinked under water bath conditions of 70~85℃ and stirring continuously at a speed of 200~400pm to obtain a mixed slurry; (4) Molding: The mixed slurry is poured onto a smooth substrate by casting, and the thickness is controlled to be 0.05~0.5mm. Then it is placed in a drying oven at 50~70℃ for casting, or the mixed slurry is injected into a mold for injection molding. (5) Post-processing: The molded material is removed and placed in a constant temperature and humidity chamber for equilibration treatment for at least 24 hours to obtain the fully biodegradable composite material.

4. The method for preparing the fully biodegradable composite material according to claim 3, characterized in that, In step (1), the liquid medium is a mixture of deionized water and carboxymethyl cellulose homogenate with a mass fraction of 1% at a volume ratio of 1:

1. The amount of the liquid medium is 2.5 to 3.5 times the total mass of bamboo nanopowder, carboxymethyl starch, cellulose nanocrystals, sodium citrate, sodium hydroxide and sodium trimetaphosphate. The preheating temperature of the liquid medium is 50 to 60°C.

5. The method for preparing the fully biodegradable composite material according to claim 3, characterized in that, In step (2), the low-speed stirring speed is 300~500 rpm.

6. The method for preparing the fully biodegradable composite material according to claim 3, characterized in that, In step (3), the cross-linking reaction takes 30 to 90 minutes.

7. The method for preparing the fully biodegradable composite material according to claim 3, characterized in that, In step (4), the substrate is a glass plate or a polyester film.

8. The method for preparing the fully biodegradable composite material according to claim 3, characterized in that, In step (5), the temperature of the constant temperature and humidity chamber is 20~25℃ and the humidity is 45~55%.

9. The application of a fully biodegradable composite material as described in claim 1 or 2 in the preparation of agricultural mulch films.

10. The application of a fully biodegradable composite material as described in claim 1 or 2 in the preparation of food packaging materials.